Resolution of an Atypical Gingival Swelling Unrelated to Plaque and Tartar Treated with Probiotics of the Lactobacillus reuteri Group: A Long-term Success - Giovanna Mosaico; Alessio Chirulli; Antonia Sinesi; Luca Vigano; Cinzia Casu (Current Approaches in Science and Technology Research Vol. 1, 2021)
In the oral cavity, the most frequent gum diseases are those of the mucous type, but also those that are less often correctly diagnosed. In fact, many of them appear in a completely similar way and are morphologically difficult to distinguish, even when they are determined by various factors, different in etiology and pathogenesis. We present a case of atypical gingival swelling unrelated to plaque and tartar, successfully treated in the long term with the probiotics Lactobacillus reuteri (L. reuteri).